Evidence-Based Pedagogy: Criteria for Experimental Research - Zhanna V. Puzanova; Vladimir M. Filippov; Maria A. Simonova; Natalia A. Grigorieva (Peoples' Friendship University of Russia (RUDN University), 2024)
The article presents approaches to defining quality criteria for pedagogical experimental research. Particular attention is paid to the evidence-based approach in pedagogy. It is argued that pedagogical research today is an integral part of the educational process and dissertations on pedagogical sciences. However, it should be noted that there are problems with the quality of such studies, which constitute a significant share of the total number of defended dissertations, and this causes an urgent need to develop methodological principles and criteria for assessing their quality. But it is not every pedagogical research that is the subject of this paper: its focus is on the methodological foundations of experimental pedagogical research or simply experimental research in pedagogy, which often do not meet the requirements of the scientific method. The authors analyzed the main topics of pedagogical research in Russia and abroad. The key results and conclusions of the study are the complex requirements for dissertations as a scientific product and pedagogical research, which determine the algorithm for obtaining proven, reliable data used in science. It is concluded that experimental research in the field of pedagogy should be carried out in accordance with the requirements for all empirical research. In particular, special attention is paid to ethical issues of pedagogical research and procedures for implementing the experimental method.